Factors affecting classroom participation: a case study of TESL foundation students / Zafirah Hanis Abdul Razak - Abdul Razak, Zafirah Hanis (2014)
The case study was conducted to examine the patterns of student classroom participation. The study was also conducted to find out the factors that affect students’ participation in the classroom. Using observation and interview, the data were collected from 24 first-year TESL students consisting of 18 females and 6 males. The findings revealed that the most common pattern of participation is responding to lecturer’s questions after being prompted. It was found that majority of the students would not take part in whole-class discussions unless asked or prompted by the lecturer. Other behaviours like volunteering to respond to lecturer’s questions (without being prompted) and giving opinions, comments etc. without being asked were commonly found. In addition, it was also found that students who contributed actively in whole-class discussions sat in front whereas those who were least active preferred to sit at the back of the classroom. The study also revealed that factors which affect students’ participation in the classroom were interrelated. The identified five interrelated factors were pedagogical, cognitive, linguistic, affective, and socio-cultural.